2009
DOI: 10.1002/cjce.20223
|View full text |Cite
|
Sign up to set email alerts
|

Steam methane reforming in a Ni/Al2O3 catalyst: Kinetics and diffusional limitations in extrudates

Abstract: The true kinetics of methane steam reforming was measured in powder of Ni/Al 2 O 3 catalyst ("Octolyst 1001" from Degussa) at different temperatures (733-890 K) for several operating conditions. New reaction rate constants were determined for this catalyst. The observed reaction rate was measured on catalyst extrudates to determine diffusion effects within the porous structure of the particle. A non-isothermal model with diffusion was used to determine effectiveness factors for each reaction. The objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 129 publications
(285 reference statements)
1
64
0
Order By: Relevance
“…The temperature decrease is more pronounced in the initial section of the catalyst bed where the 6. Comparison between the carbon dioxide selectivity ðS CO2 Þ and hydrogen yield ðY H2 Þ using the catalyst in this work and the commercial catalyst from Degussa (Oliveira et al, 2009). Results obtained with the catalysts in powder form.…”
Section: Fixed Bed Experiments With Extrudatesmentioning
confidence: 97%
“…The temperature decrease is more pronounced in the initial section of the catalyst bed where the 6. Comparison between the carbon dioxide selectivity ðS CO2 Þ and hydrogen yield ðY H2 Þ using the catalyst in this work and the commercial catalyst from Degussa (Oliveira et al, 2009). Results obtained with the catalysts in powder form.…”
Section: Fixed Bed Experiments With Extrudatesmentioning
confidence: 97%
“…It is found that the velocity across the pellet is zero. The pressure has been calculated from Darcy's law, i.e., Equation (32). So, the pressure gradient is directly proportional to the velocity.…”
Section: Intra-particle Mass Diffusion Modelsmentioning
confidence: 99%
“…Furthermore, the possibility of negative or asymptotic values of effectiveness factor cannot be ruled out for the SMR process. [7,25,29,31,32] Stutz et al [33] and Parisi and Laborde [34] have studied the catalytic surface reaction for the steam methane reforming reaction. Lutz et al [35] and Jannelli et al [36] have investigated the steam reforming system using the thermodynamic equilibrium state.…”
mentioning
confidence: 99%
“…It is clear from Fig. 2(a)-(c) that each catalyst has its own metal clusters on the support with various sizes [35].…”
mentioning
confidence: 96%